Removal of Lead and Nickel from Polluted water using L-Cysteine and L-Methionine Modified Silica gel - Etembet Desta (ASTU, 2021)
Heavy metals are inorganic pollutants of water that cause a health risk if taken at above recommended levels. The objective of this study was to use activated silica gel (SiO2), modified activated silica gel with L-cysteine (SiO2-Cys), L-methionine (SiO2-Meth), and a mixture of L-cysteine and L-methionine (SiO2-(L-Cys + L-Meth)) for adsorptions of lead and nickel ions from aqueous solution. Activated silica gel and its modified forms were prepared and characterized by Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Scanning electron microscopy (SEM), and Brunauer-emmett-teller method (BET). It was observed that increasing in surface area form BET result of SiO2-(L Cys + L-Meth) (772.816 m²/g) and SiO2-meth (730.710 m²/g) than SiO2(629.425 m²/g) and it was also supported by SEM result. Pb (II) and Ni (II) removal efficiency of SiO2, SiO2- Cys, SiO2-Meth, and SiO2-(L-Cys + L-Meth), were investigated using a batch adsorption technique. Experimental parameters such as pH of the solution, contact time, initial Pb and Ni ions concentration in solutions, and adsorbent dosage were also studied carefully. Those maximum removal efficiencies showed that 97.15 % observed at pH 6, 90 min contact time, 0.8 g/L of adsorbent dose, and 2 mg/L initial concentration for lead ion removal while 100% removal of 0.645 mg/L Pb+2 from wastewater taken from Eastern industry zone (EIZ). The highest removal efficiency of Ni (II), 99.35 % was observed at pH 5, 60 min contact time, 0.4 g/L of adsorbent dose, and 2 mg/L initial concentration using SiO2-(L-Cys + L-Meth) adsorbent. Through this optimum condition, kinetic and isotherm of the adsorption process were studied using different models. The result revealed that the kinetics of the process fitted well with the Pseudo-second-order kinetic model for lead and nickel ions. From the tested isotherm model, the Langmuir isotherm model was found to be the best fit for Pb (II), and the Freundlich model was found to be the best fit for Ni (II). From the results notably, the adsorbent SiO2-(L-Cys + L-Meth) can be regenerated continuously without affecting its extraction percentage. The removal efficiency of SiO2-(L Cys + L-Meth) decreased as the cycles increased was observed. Removals of Pb (II) and Ni (II) ions are improved using modified ASG with a mixture of L-cysteine and L methionine (SiO2-(L-Cys + L-Meth)).
Keywords: Activated Silica gel, Modification, Methionine, Cysteine, Lead (II), Nickel (II), Adsorption